On- Farm Evaluation of Candlewood Zanthoxylum Xanthoxyloides (Lam.) on Two Stored Product Pests. - Koomson, C.K. (University of Ghana, 2003)
The biological activity of dry, ground plant parts (dust) and tablets of Zanthoxylum xanthoxyloides (Lam.) was assessed in both the laboratory and on the field against the maize weevil, Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) and the cowpea weevil, Callosobruchus maculatus (F.) (Coleoptera: Bruchidae). Dry ground leaves, bark and roots were prepared in various proportions of 60% leaves and 40% roots; 70% leaves and 30% roots; 80% leaves and 20% roots; 90% leaves and 10% roots; 60% leaves and 40% bark; 70% leaves and 30% bark; 80% leaves and 20% bark; 90% leaves and 10% bark, as well as 100% leaves, 100% bark and 100% roots. These proportions were mixed with 5 kg of grains at 5% (wt/wt) concentration to assess contact toxicity, grain protection, effect on eggs and immature stages and persistency. The biological activity of Z xanthoxyloides was also accessed using tablets made from different concentrations of 2.2ml leaves and 1.8ml roots; 2.4ml leaves and 1.6ml roots; 2.6ml leaves and 1.4ml roots; 2.8ml leaves and 1,2ml roots; 2.2ml leaves and 1.8ml bark; 2.4ml leaves and 1.6ml bark; 2.6ml leaves and 1.4ml bark and 2.8ml leaves and 1.2ml bark. Five tablets of each of the different concentrations were mixed with 5 kg of grains to assess toxicity or grain protection by fumigation, effect on eggs and immature stages persistency and repellency. The effective combinations of dry ground dusts were 60% leaves and 40% roots; 70% leaves and 30% roots; 60% leaves and 40% bark and 70% leaves and 30% bark. These significantly (P<0.001) induced over 68 % mortality of both species of insects, provided about 96% protection to the grains, inhibited the development of eggs and immature stages and were persistent for 2 months. The effective tablet formulations were from concentrations of 2.2 ml: 1.8ml (v/v) leaves: roots; 2.4 ml: 1.6 ml (v/v) leaves: roots; 2.2 ml: 1.8ml (v/v) leaves: bark and 2.4 ml: 1.6ml (v/v) leaves: bark. These induced about 50% mortality, offered about 95% protection to the grains and evoked repellent actions against both insects. There was however, a rapid loss of activity after 7 days following treatment, irrespective of the dosage applied. Z xanthoxyloides, which is relatively safe to mammals because it is used for the treatment of ailments like tooth aches, stomach aches, leprous ulceration, and ulcers, syphilitic sores, fever, post-delivery pains while the leaves are fed to ruminants could be prepared into effective dry ground dust proportions as well as tablets for resource-poor farmers to protect their grains against some stored product pests.
Thesis (MPhil) - University of Ghana, 2003